Pharmaceutical preconditioning with nitric oxide synthase and L-arginine in ischemic tissues - Gazyakan, Emre; Hirche, Christoph; Reichenberger, Matthias; Germann, Günter; Engel, Holger (Annals of plastic surgery, 2020)
Background - Nitric oxide (NO) is a multifunctional signaling molecule involved in regulating vascular tone and tissue oxygenation. It is also an important cytoprotective agent against ischemia-reperfusion injury (IRI). Enhancing NO bioavailability via exogenous NO synthases (NOSs) and L-arginine promotes conversation to NO, circumventing the problem of nonfunctioning NOSs under hypoxic and acidic conditions. In this study, the authors evaluated the therapeutic efficacy of neuronal, inducible, and endothelial NOS and L-arginine on reperfusion-induced skin flap alterations. - Methods - The vascular pedicle isolated rat skin flap model was used and underwent 3 hours of ischemia. At 30 minutes before ischemia, normal saline, endothelial-, inducible-, and neuronal NOSs (1/2 IU) and L-arginine (100 mg/kg body weight) were administered by means of intravenous infusion. The IRI-induced alterations were measured 5 days after the operation. - Results - The 3 isoforms of NOS increased the flap vitality rate (VR) from 10% to 23% compared with the control group. L-Arginine treatment also increased the VR by approximately 15%. The combination of L-arginine with NOS resulted in even higher flap VRs. The best results could be achieved with the combination of endothelial NOS (2 IU) and L-arginine. - Conclusions - Modulation of NO bioavailability via exogenous application of NOSs and L-arginine significantly improved VRs in a skin flap rat model. This pharmacologic preconditioning has the potential to attenuate IRI-induced alterations in skin flaps.
Gesehen am 27.04.2020